Chemical JAK inhibitors for the treatment of rheumatoid arthritis. (1st November 2016) - Nakayamada, Shingo; Kubo, Satoshi; Iwata, Shigeru; Tanaka, Yoshiya
ABSTRACT: Introduction: Considerable advances in the treatment of rheumatoid arthritis (RA) have been made following the advent of biological disease-modifying anti-rheumatic drugs (DMARDs). However, biological DMARDs require intravenous or subcutaneous injection and some patients fail to respond to these drugs or lose their primary response. Currently, Janus kinase (JAK) inhibitors have been developed as a new class of DMARD that inhibits the non-receptor tyrosine kinase family JAK involved in intracellular signaling of various cytokines and growth factors. Areas covered: Several JAK inhibitors such as tofacitinib and baricitinib are oral synthetic DMARD that inhibit JAK1, 2 and 3. Both drugs have shown feasible efficacy and tolerable safety. In this article, efficacy and adverse events from the phase III trials of JAK inhibitors are overviewed. In addition, pharmacokinetics and mechanism of action of JAK inhibitors in relevance to efficacy and adverse events are covered. Expert opinion: JAK inhibitors are novel therapies for RA that inhibit multiple cytokines and signaling pathways. Further studies are needed to determine their risk-benefit ratio and selection of the most appropriate patients for such therapy.